UPAYA GURU DALAM PEMBENTUKKAN KARAKTER PERCAYA DIRI SISWA SEKOLAH DASAR - Niken Rizkiani; Meilan Tri Wuryani; Ade Bagus Primadoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Self-confidence is a crucial aspect in elementary school student development, particularly in fostering courage, independence, and active participation during learning. Initial findings at SD Negeri 1 Weleri, though, showed that certain fourth-graders still struggled with self-confidence, demonstrated by their reluctance to share thoughts, anxiety when presenting, and passive engagement in class. This highlights the necessity for teachers to offer increased support and encouragement to help students acknowledge their strengths. Consequently, this research seeks to thoroughly investigate the self-confidence levels of fourth-grade students at SD Negeri 1 Weleri, assess the strategies teachers employ to nurture this confidence, and pinpoint factors that either aid or impede its development within the school setting. A qualitative research approach, utilizing a descriptive design, was adopted. Participants included fourth-grade teachers, the school principal, and the students themselves. Data was gathered through document analysis, direct observation, and detailed interviews. The validity of the data was established through source triangulation and participant verification. An interactive data analysis model encompassing data reduction, data presentation, and conclusion formation was used. The study’s findings are expected to enhance teachers’ understanding of how to create a secure, comfortable, and encouraging learning atmosphere, enabling students to feel appreciated, express themselves freely, and develop self-confidence as a crucial component of their overall development.